2013
DOI: 10.1002/bdrb.21078
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Assessment of a New Human Embryonic Stem Cell‐Based Biomarker Assay for Developmental Toxicity Screening

Abstract: A metabolic biomarker-based in vitro assay utilizing human embryonic stem (hES) cells was developed to identify the concentration of test compounds that perturbs cellular metabolism in a manner indicative of teratogenicity. This assay is designed to aid the early discovery-phase detection of potential human developmental toxicants. In this study, metabolomic data from hES cell culture media were used to assess potential biomarkers for development of a rapid in vitro teratogenicity assay. hES cells were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 56 publications
(35 reference statements)
3
76
0
Order By: Relevance
“…Significant advances have been made particularly in the further simplification of the test battery, while still being able to identify reproductive toxic chemicals efficiently, either in isolation [25], or in a grouping context [41,43]. We found that even with a relatively small number of tests, either apical tests combined with mechanistic tests or an relatively small number of mechanistic tests predictivities ranging from 74 to 94% can be reached [20,25], which is comparable to that obtained with much larger ToxCast screening panels [21], the ReProTect battery [7], or the zebrafish ELS tests [49], a human embryonic stem cell test [50]. This is remarkable, since the concordance between different test species, like rabbit and rat has been estimated to be not more than 60% [6].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Significant advances have been made particularly in the further simplification of the test battery, while still being able to identify reproductive toxic chemicals efficiently, either in isolation [25], or in a grouping context [41,43]. We found that even with a relatively small number of tests, either apical tests combined with mechanistic tests or an relatively small number of mechanistic tests predictivities ranging from 74 to 94% can be reached [20,25], which is comparable to that obtained with much larger ToxCast screening panels [21], the ReProTect battery [7], or the zebrafish ELS tests [49], a human embryonic stem cell test [50]. This is remarkable, since the concordance between different test species, like rabbit and rat has been estimated to be not more than 60% [6].…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, it seems also likely that chemicals often address multiple pathways of toxicity, thereby reducing the need to have all possible mechanism of action included in a final battery. This is supported by the very good performance of our battery, even when compared with much larger batteries [21] or more integrative lower throughput batteries and tests [7,49,50]. At present the current combination of apical and HTS tests seems a pragmatic and effective choice that can be further improved when more mechanisms of reproductive toxicity become known.…”
Section: Discussionmentioning
confidence: 63%
“…While our in vitro panel was not 100% accurate at detecting cardiotoxicity, the lack of false positives and the high sensitivity generated from our xCELLigence testing (88.9%) suggest that these tests provides a robust method for early evaluation of cardiac liability. To date, other in vitro preclinical testing methods also show b100% statistical correlation for drug-induced toxicity (Pointon et al, 2013;Guo et al, 2013;Sirenko et al, 2013;Palmer et al, 2013;Morton et al, 2014;van de Water et al, 2011), and it is unlikely that any preclinical test would have 100% accuracy. A variety of differences (i.e., metabolites generated or patient-specific genetic predispositions) in exposed patient populations that cannot be recapitulated fully in vitro make exact prediction difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Other screening tools that can be used include in vitro estrogen receptor/androgen receptor transactivation assays and the in vitro aromatase assay, which can help identify potential endocrine disrupting compounds. For developmental toxicity prediction, a number of predictive assays have been promulgated over the years including transcriptome profiling of in vitro systems, mammalian whole embryo culture, zebrafish embryo exposures, and embryonic stem cell metabolomics [9,10]. These predictive tools can be used in a screening program to identify compounds of potential concern, not only just for pesticides but for chemicals in general.…”
Section: Typical Flow and Integration Of Studies For Agrochemicalsmentioning
confidence: 99%